Is OSPAR 98/3 science-based politics or politics-based science? - Paces, Nicole; Davies, Abigail J.; Hastings, Astley (Frontiers in Marine Science, 2024)
Man-made structures in the marine environment such as offshore Oil & Gas infrastructure are known to provide a hard substrate that enables ecosystems to develop on and around them. Current decommissioning practices on the UK Continental Shelf are mandated by the OSPAR Decision 98/3 with the premise of a clean seabed at its core, meaning that it is the expectation that all infrastructure is completely removed at the end of its operation life, leaving a clear seabed behind. This study critically reviewed 49 peer-reviewed articles relating to the ecosystem and the impact to these ecosystems by current removal practices. The results clearly demonstrate that current science-based evidence shows that existing O&G platform substructures act as multipurpose artificial reefs upon which rich ecosystems have developed and that their removal degrades the overall North Sea marine environment. Furthermore, this study shows that clear-sea bed policies, such as OSPAR 98/3, do not reflect, nor understand the complex relationship and interdependencies between biology and manmade structures and do not reflect current scientific knowledge.It is concluded that based on current knowledge, it is no longer scientifically justifiable to mandate the removal of all O&G infrastructure during decommissioning and that applying the principle of a clean seabed according to the OSPAR Commission should be re-considered.